FIQIH PARENTING ; MEMBANGUN POLA PENGASUHAN ANAK ISLAMI MELALUI AKTIFITAS PEMBELAJARAN DI PERGURUAN TINGGI - Idrus Idrus (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2020)
This paper explains about efforts to build patterns of Islamic childcare through the learning activities of Parenting Fiqh in higher education institutions. This research uses library research, while the data are obtained from printed, non-printed books, magazines or articles. Higher education as one of the places to gain advanced knowledge or development, is one place where students get preliminary knowledge about how to build Islamic childcare patterns, namely patterns of care that are in accordance with the Qur'an and Sunnah. This can be obtained by students in learning activities in the Fiqh Parenting course, in which integrated Islamic content, psychology, moral and social education.